ON THE SCHOOL AND PRACTICAL THE CORPORAL ONES IN DIVERSITY SÓCIO-CULTURAL (Fiep Bulletin - online, 2014)
Summary: The present text is fruit of a work in permanent process of inquiry. One is about an analysis of the reality of the education escolarizada in Brazil, in particular in the State of the Espirito Santo, where the organization of the pedagogical work happens of form conservative, front to the production process and preservation of manifestations of popular culture in the field of practical the corporal ones, over all of the Dances, the Games and the popular Tricks in a considerable amount of communities that are taken care of by public schools. At the moment the work presents a quarrel concerning the context on the logic of the pertaining to school organization in Brazil at its historical moments of social formatting, emphasizing the secularized education as central instrument of formation of the new man for the new country. We present, from a research metodologicamente associated between the bibliographical quantity, the comment of the reality and the practical analysis of the pedagogical one of the schools installed in active communities in the field of the cultural manifestations that preserve the popular Dances, Games and tricks. As result of the investigativo work, we point the significant existence of active communities, that possess schools and establish corporal direct relations between its practical and the leisure and the partner-economic production, thus obtaining, to preserve the culture and the religiosidade. On the other hand, we more assay notes for an analysis deepened concerning the conflict relations between the knowledge produced for the communities and the curricular organization of the school.
Keywords: School; Popular culture; Practical corporal